Challenges for Global Learners: A Qualitative Study of the Concerns and Difficulties of International Students - Gautam, Chetanath; Lowery, Charles L.; Mays, Chance; Durant, Dayan (Journal of International Students, 2016)
The authors in this study seek to inform academia about international students’ experiences and challenges while attending universities in Small Town USA. Despite their eagerness to study in the United States (U.S.), international students are faced with setbacks that many universities fail to recognize or realize. The researchers conducted in-depth interviews with a purposive sample of students using questions based on information from the literature and an initial survey. The themes that emerged from the data analysis were language, jobs/finances, transportation, assimilation, religious interactions, and identity. Findings emphasize the imperative to understand the challenges these students face as they continue their educational journeys in the United States.